A sandwich enzyme-linked immunosorbent assay for human plasma apolipoprotein A-V concentration - Mitsuaki Ishihara; Takeshi Kujiraoka; Tadao Iwasaki; Makoto Nagano; Mayumi Takano; Jun Ishii; Masahiro Tsuji; Hajime Ide; Irina P. Miller; Norman E. Miller; Hiroaki Hattori (Journal of Lipid Research, 2005)
Apolipoprotein A-V (apoA-V) is a recently discovered apolipoprotein that appears to have a role in plasma triglyceride (TG) transport. We have developed an ELISA for apoA-V using monoclonal antibodies that has a lower limit of detection of 0.3 ng/ml and linearity up to 20 ng/ml. The ELISA was then used to quantify plasma apoA-V in 196 healthy subjects and 106 patients with insulin-resistant diabetes mellitus. In the healthy subjects, total apoA-V concentration was 179.2 ± 74.8 ng/ml, and it was greater in females than in males (P < 0.005). It was correlated positively with the plasma HDL cholesterol (r = 0.32, P < 0.0001), apoA-I (r = 0.27, P = 0.0001), and apoE (r = 0.18, P = 0.011) concentrations and negatively with plasma TG concentration (r = −0.22, P = 0.021). In relation to single nucleotide polymorphism 3 (−1131C/T) of the apoA-V gene, apoA-V concentration was higher in the T/T type than in the C/C type (P < 0.01). Plasma TG concentration was lower in the T/T type than in the C/C or C/T type (P < 0.05).ApoA-V concentration was lower in the diabetic patients (69.4 ± 44.3 ng/ml; P < 0.01) than in the healthy controls.